(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The study aimed to determine the availability of the dimensions of ethical competition represented by (reference to the ethical code, use of free hotlines regarding ethical problems, ethical training, and ethical intelligence) in the Nineveh Agriculture Directorate, based on the answers of the respondents about these dimensions and the descriptive analytical approach was adopted in processing the data. It was collected through a questionnaire form that was distributed to a random sample of (50) respondents from the functional staff in the organization under study. Several statistical methods were used in analyzing this data according to ready-made programming (SPSS v26), including (percentages, arithmetic mean, standard deviation, coefficient of difference, t-test results, relative significance) The research reached several conclusions, most notably the availability of dimensions of moral competition with a clear discrepancy between the answers of the respondents about those dimensions at the level of the organization under study. In addition, a number of proposals were presented emphasizing legitimacy and an effective amount of interest in the dimensions of moral competition so that the features of this interest become clear and what It leads us to adopt dimensions that go beyond the familiar contexts so that the researched organization has the opportunity to add new dimensions that are in line with contemporary developments.